Mental fatigue impairs soccer-spcific performance - Smith, M.; Marcora, S.; Lenior, M.; Badin, O.; Merlini, M.; Deprez, D.; Zeuwts, L.; Coutts, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Anecdotal reports from soccer players and coaches suggest that mental fatigue impairs soccer performance. However experimental investigations of this claim are limited. Therefore, two randomised, crossover investigations were conducted to assess the impact of mental fatigue on soccer-specific physical, technical, and decision-making performance. Methods: Players completed a 30-min Stroop task (mental fatigue treatment), or 30 min of an emotionally neutral control, prior to tests of soccer-specific performance. Study 1 assessed the impact of mental fatigue on physical and technical performance of 20 well-trained soccer players during 15-min, 5 vs. 5 small-sided games (SSGs). Physical performance was assessed using 15-Hz GPS units, and technical performance was assessed using video-based notational analysis. Heart rate (HR) and ratings of perceived exertion (RPE; CR10) were also recorded during the SSGs. Study 2 utilised videos of simulated play to assess the impact of mental fatigue on soccer-specific decision-making, and visual search behaviour in 12 well-trained soccer players. Decision-making skill was assessed using response time and accuracy, while visual search behaviour was assessed via search rate, fixation location, and fixation order. A progressive magnitude-based approach was used to assess chances of differences between conditions being trivial or true (greater than the smallest worthwhile change; 0.2 × the between-subjects SD). Results: Players reported higher levels of mental fatigue following the Stroop task than the control treatment in both studies, while no clear differences in motivation existed. Mental fatigue had unclear effects on most physical performance variables in Study 1, despite a possibly lower HR (mental fatigue = 85 ± 5%HRmax; control = 86 ± 4%HRmax; ES = -0.28), and likely higher RPE in the mental fatigue condition (mental fatigue = 6.8 ± 1.4; control = 6.2 ± 1.6; ES = 0.39). In contrast, mental fatigue impaired both offensive and defensive technical performance during the SSGs (positive involvements: mental fatigue = 70 ± 10%; control = 63 ± 9%; ES = -0.73). In Study 2, mental fatigue very likely reduced soccer-specific decision-making accuracy (mental fatigue = 81 ± 6%; control = 86 ± 4%; ES = -0.89) and likely increased response time (mental fatigue = 768 ± 134 ms; control = 685 ± 156 ms; ES = 0.49), despite minimal differences in visual search behaviour. Discussion: These findings support anecdotal reports that mental fatigue impairs soccer-specific performance. Soccer clubs may benefit from assessing pre-match routines, to ensure players are not mentally fatigued prior to competition, and are advised to identify and implement strategies that may attenuate the negative impact of mental fatigue on performance. In this respect, coaches could utilise short SSGs to train technical performance under mentally fatigued conditions, without compromising physical training loads.